Working on Critical Thinking skills using the computer lab works of an Engineering subject - Juan Giner-Navarro; Águeda Sonseca; José Martínez-Casas; Javier Carballeira (Multidisciplinary Journal for Education, Social and Technological Sciences)
A practical intervention was devised in order to promote and to assess Critical Thinking in undergraduate students of Engineering. First, in collaboration with specialists in education, the concept of Critical Thinking, and its skills and dispositions on which to focus on, was determined. Second, a teaching strategy was designed in order to be as effective as possible, considering the limitations of the intervention. This strategy took advantage of the computer lab sessions where discussion and questioning encouraged the development of Critical Thinking. Then, the instruments to assess the acquired skills and attitudes of the students were developed. Finally, a quantitative analysis of the results was conducted in order to evaluate the validity and reliability of the strategy. This paper presents a full description of the intervention carried on for two years. Besides the desired effects on the students’ performance, some conclusions regarding the development of appropriate instruments to deal with a large group of students are drawn. This intervention has proven to be effective in order to help the students to develop their Critical Thinking skills, and it is particularly suitable for large groups.